Performance Measurement of Customer Relationship Management (CRM) Using The CRM Scorecard Method in CV. Lestari Motorindo Jaya Indralaya - Risma Damayanti; Ali Ibrahim; Mira Afrina (Jurnal Sistem Informasi, 2021)
The measurement of customer relationship management (CRM) performance is very necessary to find out how much the level of performance of CRM in the company. CV. Lestari Motorindo Jaya Indralaya is a CV that is engaged in the sale of motorcycles, spare parts, and Honda motorcycle services located in Ogan Ilir Regency. The purpose of this study is to Evaluate and Also know the performance of CRM on CV. Lestari Motorindo Jaya Indralaya by using the CRM Scorecard. There are four perspectives on the CRM Scorecard method items, namely customer value, customer satisfaction, customer interaction, and customer knowledge. CRM performance measurement results in CV. Lestari Motorindo Jaya Indralaya is 3,937 in the Likert scale means having good performance. The measurement results that have low values are found in the customer interaction perspective, the which is 2.75.Keywords: Customer Relationship Management (CRM), CRM Scorecard, Performance Measurement